Assessment of Aggression among High Schools Students (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Aggression is a behavioral characteristic that refers to forceful actions or procedures (such adeliberate attack) with intentions to dominate or master. It tends to be hostile, injurious, or destructive, andis often motivated by frustration for an individual, aggressive behavior is considered understandable andnormal under appropriate circumstances, but when it is frequent, intense, lasting, and pervasive, it is morelikely to be a symptom of a mental disorder. Likewise, aggression between groups, can be in the form ofhealthy competition, but can become harmful when unfair or unjust disadvantage or frustration is perceived,leading to hostility. Objectives: assessment aggression among high school students. Methodology: Adescriptive cross-sectional study was carried out in order to achieve the stated objectives. The study hasbegun from 1st September 2018. Settings of the Study: The settings of the study include (41) High secondaryschools which are distributed in (3) Districts of Al-Najaf Governorate, urban (23) schools and rural (18)schools, these schools are systematic randomly selected. Results: most majority was moderate aggressiveby 52.7%. Conclusions: this study show which included an overall assessment of Aggressive, where thestudy showed that the most majority was moderate aggressive. Recommendations: Supporting educationalmethods by the Educational Committee that limits aggressive behavior of adolescents in schools, such as(moving away from scenes of an aggressive nature, beating, violence, fighting, quarrels, and blood scenes).And The teacher devotes part of the lesson time to clarifying issues and harms of aggression, and to show thebenefits of tolerance and contentment. and The school administration cooperated with the teenager’s familyto identify the causes of his aggression. Finally, The Ministry of Education is working to create posters thatreject aggression and suspend it throughout the school.